Flux Crystal Growth, Crystal Structure, and Optical Properties of New Germanate Garnet Ce2CaMg2Ge3O12 - Chen, Jie; Yan, Hong; Kuwabara, Akihide; Smith, Mark D.; Iwasa, Yuki; Ogino, Hiraku; Matsushita, Yoshitaka; Tsujimoto, Yoshihiro; Yamaura, Kazunari; zur Loye, Hans-Conrad (Frontiers in Chemistry, 2020)
A new germanate garnet compound, Ce2CaMg2Ge3O12, was synthesized via flux crystal growth. Truncated spherical, reddish-orange single crystals with a typical size of 0.1–0.3 mm were grown out of a BaCl2–CaCl2 melt. The single crystals were characterized by single-crystal X-ray diffraction analysis, which revealed that it adopted a cubic garnet-type structure with a = 12.5487(3) Å in the space group Ia–3d. Its composition is best described as A3B2C3O12, where Ce/Ca, Mg, and Ge occupied the A, B, and C sites, respectively. A UV–vis–NIR absorption spectroscopy measurement on the germanate garnet revealed a clear absorption edge corresponding to a band gap of 2.21 eV ( = 561 nm). First-principle calculations indicated that the valence band maximum was composed of Ce 4f bands, whereas the conduction band minimum mainly consisted of Ce 5d bands. These findings explain the observed absorption edge through the Ce 4f → 5d absorption. Photoluminescence emission spectra exhibited a very broad peak centered at 600 nm, corresponding to transition from the lowest energy d level to the 4f levels.